Mitochondrial DNA and Distribution Modelling Evidenced the Lost Genetic Diversity and Wild-Residence of Star Tortoise, Geochelone elegans (Testudines: Testudinidae) in India - Shantanu Kundu; Tanoy Mukherjee; Ah Ran Kim; Soo-Rin Lee; Abhishek Mukherjee; Won-Kyo Jung; Hyun-Woo Kim (Animals, 2022)
The Indian star tortoise (Geochelone elegans) is a massively traded animal in South Asia. To mitigate this risk, the conservation agencies recommended guidelines to safeguard this charismatic species in nature. We adopted mitochondrial DNA-based investigation and performed species distribution modeling of G. elegans throughout its distribution range in the Indian subcontinent. The genetic analyses revealed weak genetic landscape shape interpolations, low intraspecific distances (0% to 1.5%) with mixed haplotype diversity, and a single molecular operational taxonomic unit (MOTU) in the cytochrome b gene dataset. The star tortoise, G. elegans, and its sister species Geochelone platynota showed a monophyletic clustering in the Bayesian (BA) phylogeny. We also attempt to understand the habitat suitability and quality of G. elegans in its distribution range. Our results suggest that, out of the extant area, only 56,495 km2 (9.90%) is suitable for this species, with regions of highest suitability in Sri Lanka. Comparative habitat quality estimation suggests the patch shape complexity and habitat fragmentation are greater in the western and southern ranges of India, which have been greatly influenced by an increased level of urbanization and agriculture practices. We have also provided a retrospect on the potential threat to G. elegans related to the wildlife trade on the regional and international spectrum. Our results detected multiple trading hubs and junctions overlying within the suitable ranges which need special attention in the vicinity. The present study calls for a proper conservation strategy to combat the fragmented distribution and explicitly recommends intensive genetic screening of founder individuals or isolated adult colonies, implementing scientific breeding, and subsequent wild release to restore the lost genetic diversity of star tortoises.